2019
DOI: 10.3390/fluids4040193
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Hyaluronic Acid Concentration in Normal and Osteoarthritic Equine Joints

Abstract: Osteoarthritis (OA) is the most common major disabling disease in humans and horses. Hyaluronic acid (HA), naturally abundantly present in synovial fluid (SF), is thought to have crucial impact on the functional rheological and biochemical features of SF in healthy and osteoarthritic joints. Here we present comparative measurements of HA concentration in SF from 35 normal and osteoarthritic equine joints, between two different approaches. On the one hand, an established biochemical HA-specific Enzyme–Linked Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The results showed that the spectral signals of SF in patients with different grades of OA differed. HA, a main component of SF, is an important biomarker in the diagnosis of OA [ 112 , 113 ]. With the development of OA, the amounts of amide III (1250 cm −1 ) and C–C, C–O bonds (1155 cm −1 ) in HA increased [ 114 ], which showed the potential of Raman spectroscopy in relation to the diagnosis of OA by SF analysis.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…The results showed that the spectral signals of SF in patients with different grades of OA differed. HA, a main component of SF, is an important biomarker in the diagnosis of OA [ 112 , 113 ]. With the development of OA, the amounts of amide III (1250 cm −1 ) and C–C, C–O bonds (1155 cm −1 ) in HA increased [ 114 ], which showed the potential of Raman spectroscopy in relation to the diagnosis of OA by SF analysis.…”
Section: Raman Spectroscopymentioning
confidence: 99%